Comparison of porcine and human lumbar spine flexion mechanics* - Dickey, J. P.; Dumas, G. A.; Bednar, D. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Animal models have been proposed as an alternative to human spinal specimens for in vitro mechanical testing due to the limited availability, poor reproducibility, high cost, and potential health risk associated with human specimens. The purpose of this study was to directly compare the flexion biomechanics of porcine and human lumbar spines. We determined the range of motion, laxity zone and the stiffness under pure-moment flexion loading. The porcine and human specimens showed qualitative similarities in mechanical behaviour. However the porcine specimens demonstrated a number of quantitative differences including a less-stiff, more extensive, low-stiffness region around the neutral position and a larger flexion range of motion. The results suggest that the porcine lumbar spine may be a potential model for the human lumbar spine for certain in vitro mechanical tests including comparisons between spinal fixation constructs.
Keywords: Biomechanics; animal model; porcine; human; comparative mechanics; spine; lumbar spine